The Main Characters’ Language Style Matching in To All the Boys I’ve Loved Before Movie - Tilana, Olivia (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This research aimed to investigate the use of function words, verbal mimicry, and non-verbal language styles in assessing the alignment of language styles between individuals. The film "To All the Boys I Have Loved Before" (2018) was chosen as the subject of analysis, as it depicted social dynamics that resembled real-life situations on a smaller scale. By employing the Language Style Matching theory proposed by Bowen et al. (2017), the researcher successfully identified significant matches and consistent outcomes in relation to the film's conclusion. The research approach employed both quantitative and qualitative methods, allowing for the analysis of data while providing in-depth explanations. The study utilized a Mixed Method Research (MMR) approach and yielded a final Language Style Matching score of 0.91 for verbal mimicry, indicating a nearly perfect match. Two categories of Language Style Matching emerged from the analysis, namely verbal and non-verbal mimicry. The researcher identified twelve instances of non-verbal mimicry in the film, including six motor movements, three postures, two facial expressions, and one gaze. The findings of this study revealed that the main characters in "To All the Boys I've Loved Before," namely Peter Kavinsky and Lara Jean, exhibited mutual interest and compatibility.